Media Manipulating Allegiances: The Ibrahim Babangida Regime and the Politics of Loyalty, Propaganda, and Elite Control in Nigeria - Olayinka Babatunde Adebogun; Ololade Olatunji Lateef; Omotola Ogunbola; Timothy Ekeledirichukwu Onyejelem (Budapest International Research and Critics University, 2025)
The regime of Ibrahim Badamasi Babangida (IBB), Nigeria’s military ruler from 1985 to 1993, was marked by a sophisticated strategy of political manipulation designed to consolidate power, maintain elite loyalty, and control public perception. This study examines how Babangida’s government deployed propaganda, patronage networks, and psychological tactics to shape political allegiances and suppress dissent. By leveraging state-controlled media, co-opting influential elites, and fostering a culture of political uncertainty, the regime engineered a system where loyalty was rewarded while opposition was systematically neutralized. Through an analysis of government policies, media narratives, and elite interactions during this period, the paper highlights how Babangida’s administration blurred the lines between governance and manipulation. The institutionalization of prebendalism, coupled with calculated misinformation campaigns, allowed the regime to maintain a façade of democracy while orchestrating one of Nigeria’s most prolonged transitions to civilian rule. Additionally, the annulment of the 1993 presidential election, widely regarded as free and fair, underscored the regime’s ultimate reliance on deception and control to maintain its grip on power. This paper contributes to the broader discourse on authoritarian governance in postcolonial Africa by illustrating how Babangida’s rule set a precedent for political maneuvering that continues to shape Nigeria’s democratic trajectory. It also underscores the enduring impact of elite manipulation on political institutions and public trust in governance.